Hubungan status demografi dengan pengetahuan kesehatan reproduksi pasien rawat jalan - Aziza, Nurul; Rumana, Nova Mega (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Reproductive health problems in the Bandar Lampung area remain at around 118 cases, both new and existing. Approximately 52 patients visit the Bakung Community Health Center for treatment with reproductive problems. Considering the livelihoods of the residents within the Bakung Community Health Center's coverage area, the majority are fishermen and have little knowledge about maintaining reproductive health. Purpose: To determine the relationship between reproductive health knowledge and the demographic status of outpatients at the Bakung Community Health Center. Method: The research design used was a descriptive correlation with a cross-sectional approach. This study aimed to determine the relationship between the independent and dependent variables after identifying the characteristics of each variable (Notoatmodjo, 2002). Results: Statistical tests showed a p-value of 0.000 for the education level variable, a p-value of 0.009 for the respondent's age variable, and a p-value of 0.000 for the respondent's occupation and knowledge level. Conclusion: There is a significant relationship between education level, age, and occupation and respondents' knowledge level.   Keywords: Demographics; Patients; Reproduction.   Pendahuluan : Masalah kesehatan reproduksi di wilayah Bandar Lampung masih berkisar 118 kasus baik berupa kasus baru dan kasus lama. Wilayah Puskesmas Bakung pasien yang datang untuk berobat dengan masalah reproduksi berkisar 52 orang untuk berkonsultasi tentang masalah reproduksi.  Apabila dilihat dari mata pencaharian penduduk yang berada di wilayah kerja Puskesmas Bakung, rata-rata para penduduk yang ada hanya sebagai nelayan yang mempunyai sedikit pengetahuan tentang menjaga kesehatan reproduksi. Tujuan : Untuk mengetahui hubungan pengetahuan kesehatan reproduksi dengan status demografi pasien rawat jalan di Puskesmas Bakung Metode : Desain penelitian yang digunakan adalah deskriptif korelasi dengan pendekatan cross sectional, yaitu untuk mengetahui hubungan antara variabel bebas (independen) dan variabel terikat (dependen) setelah diketahui karakteristik dari masing-masing variabel (Notoatmodjo, 2002). Hasil : Uji statistik menunjukkan p-value=0,000 pada variabel tingkat pendidikan,  p-value=0,009 pada variabel tingkat usia responden, dan p-value=0,000 pada variabel pekerjaan responden dengan tingkat pengetahuan responden. Simpulan: Ada hubungan yang signifikan antara tingkat pendidikan, usia, dan pekerjaan dengan tingkat pengetahuan responden.   Kata Kunci: Demografi; Pasien; Reproduksi.